The role of morphological complexity in predicting the learnability of an additional language: The case of La (additional language) Dutch. (January 2019) - van der Slik, Frans; Hout, Roeland van; Schepens, Job
Applied linguistics may benefit from a morphological complexity measure to get a better grip on language learning problems and to better understand what kind of typological differences between languages are more important than others in facilitating or impeding adult learning of an additional language. Using speaking proficiency scores of 9, 000 adult learners of Dutch as an additional language, we reproduced the findings of the Schepens et al. (2013a) study, using a reduced morphological complexity measure. We wanted to define a reduced measure to reveal which morphological features constitute the really important learning problems. Adult language learners whose first language (L1) has a less complex morphological feature configuration than Dutch turned out to have more learning difficulties in acquiring Dutch the less complex their L1 is in relation to Dutch. The reduced measure contains eight features only. In addition, we found cognitive aging effects that corroborate the construct validity of the morphological measure we used. Generally, adult language learners' speaking skills in Dutch improve when residing longer in the host country. However, this conclusion is only warranted when their L1 morphological complexity is at least comparable to Dutch morphological complexity. If the morphological complexity of their L1 is lower as compared to Dutch, the effect of length of residence may even reverse and have a negative impact on speaking skills in Dutch. It was observed that the negative effect of age of arrival is mitigated when adult language learners have a command of a second language (L2) with higher morphological complexity. We give morphological information for five additional target languages: Afrikaans, Chinese, English, German, and Spanish.